Seismic Performance Of A Double-Storey Prefabricated Cold-Formed Steel Structure As Post-Disaster Temporary Housing - Wong, Jia Hui (Universiti Sains Malaysia, 2021)
The community often neglects the risk of earthquake occurring in Peninsular Malaysia as the country is located away from the Ring of Fire zone. Therefore, seismic design is seldom considered during building design. Furthermore, there is a lack of research in developing a good emergency relief shelter or post-disaster housing system. Therefore, this study proposes a design of a double-storey prefabricated cold-formed steel house as a sustainable post-disaster temporary housing solution for an earthquake event. In this study, a numerical analysis of 1:2 scaled models is used to analyse their seismic performance by inputting the acceleration time history of 0.09g, 0.12g, and 0.16g recorded by KKM Seismic Station during the 2015 Ranau earthquake via ETABS software. Furthermore, two types of models were simulated, i.e., model without wall panels and model with wall panels to identify the influence of the wall panels on the structure's seismic performance. The results show that the inclusion of wall panels reduces the joint acceleration of the structure by an average of 74 %. In addition, it also reduces the joint displacement by a percentage of 7.5% (storey one) and 34% (lower roof and upper roof). However, the proposed model’s design exceeded the limit for total storey drift and inter-storey drift. Therefore, three different strengthening methods were proposed, and the most effective way to enhance the structural seismic performance is by adding two pairs of diagonal bracing at the ground floor connecting the first floor and the base of the structure in the two bays of portal frame with shorter span in the shaking direction.